“If Not Us, Who?”: Preserving Javanese Language Through Code Switching Practice in Yowis Ben Movie - Reva Caesar Margi Pangestu; Emy Sudarwati (Yayasan Visi Intan Permata, 2021)
The occurrence of Code switching phenomenon is relatively normal in bilingual and multilingual society. However, despite a large body of research on code switching, little attention has been given to code switching phenomenon in relation to language maintenance issue. This study investigates the types of code switching that are used by main characters in Yowis Ben The Series Episode 6; the main characters’ reasons to use code switching in Yowis Ben The Series Episode 6; and the investigation concerning Javanese language maintenance indication depicted in the movie. This descriptive qualitative study probes into the ways in which Javanese language as a vernacular language is used along with the standard Bahasa Indonesia in a movie.In addition to examining the types of code switching, this study also tries to go further within the issue of Javanese language maintenance the movie wants to convey. The results showed that there are a total of 20 data indicating three types of code switching in Yowis Ben The Series Episode 6: Intra-sentential switching (11), inter-sentential switching (8), and tag switching (once).The reasons of using code switching are to expresscertain feelings and attitudes, to talk about a specific topic, to express solidarity between people from different or the same ethnic groups, and to attract attention and persuade audiences.